Pengaruh Rasio LiBOB:TiO2 dari Lembaran Polimer Elektrolit sebagai Pemisah terhadap Kinerja Elektrokimia Baterai Lithium-Ion Berbasis LTO - Agriccia Pangestica Saputry; Yayuk Astuti; Titik Lestariningsih (Jurnal Kimia Sains dan Aplikasi, 2019)
LTO anode-based Ion-Lithium batteries with artificial polymer electrolyte sheets consisting of PVdF-HFP, TiO2, and LiBOB as well as commercial sheets and with electrolyte solutions LiTFSI and LiPF6 have been made by assembling method. The changing variables in this study were the ratio between TiO2 and LiBOB for separator sheets and types of electrolytes used, namely, LiTFSI and LiPF6. Some characterizations were undertaken to determine battery performance including battery voltage determination, Cyclic Voltammetry (CV) testing to measure battery cell performance, and Electrochemical Impedance Spectrometry (EIS) analysis to measure battery conductivity values. The results showed that the presence of LiBOB and TiO2 at the separator in the battery can improve the performance of LTO-based lithium batteries. Artificial separator sheets with a composition ratio of TiO2: LiBOB of 5:25 with electrolyte solution LiPF6 which produces work stress, potential difference, and ionic conductivity of 3.06 V; 0.3 V; and 1.486x10-6 Scm-1 is the best possible to be applied to lithium-ion batteries.